COPING WITH BIG CLASSES: EFFECT OF BIG BOOK IN FOURTH GRADE STUDENTS READING COMPREHENSION - Mahayanti, N.W.S.; Padmadewi, N.N.; Wijayanti, L.P.A. (Universitas Pendidikan Ganesha, 2017)
Teaching reading comprehension for young learners becomes a challenge for English teachers in Indonesia. Dealing with that problem, this study had a purpose to investigate whether there was any significant effect on studentsâ reading comprehension taught by using big book and conventional media or not. Post-test only control group was used as the design with forth grade students of SD Laboratorium Undiksha Singaraja as the population. The data were analyzed descriptively and inferentially. As the result, it can be concluded that big book gives significant effect on students reading comprehension compared with the control group. It can be proven from the difference of mean score gained by experimental group (83.56) and control group (76.19). The result of the t-test also shows that the t-observed exceeded the t-critical value (4.088 > 2.042).